2004
DOI: 10.1021/jp048343x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Structural Evidences for Charge Transfer and Localization in Iodine-Doped Pentacene

Abstract: We have investigated the doping mechanism of pentacene with iodine and its impact on the structure and on the electronic properties of single crystals, powders, and thin films in a large range of iodine concentration up to six iodine per pentacene (PEN) molecule (I/PEN = 6). Three regimes of doping have been identified. In the low doping regime I/PEN < 0.05, the pristine pentacene structure of single crystals is maintained. Electron spin resonance (ESR) evidences a Pauli susceptibility, that is, the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 38 publications
(67 reference statements)
11
49
1
Order By: Relevance
“…Since we maintain a constant average sample temperature of 300 K, the decrease in carrier concentration is expected to be linear on a log-log plot of p versus t, dropping in proportion to 1 / t ␤ , where ␤ is related to the order of the dedoping chemical reaction. 23 This dependence is consistent with the approximately linear increase measured for the Seebeck coefficient versus log͑t͒, since S ϳ ln͑p͒ through Eq. ͑2͒.…”
supporting
confidence: 87%
“…Since we maintain a constant average sample temperature of 300 K, the decrease in carrier concentration is expected to be linear on a log-log plot of p versus t, dropping in proportion to 1 / t ␤ , where ␤ is related to the order of the dedoping chemical reaction. 23 This dependence is consistent with the approximately linear increase measured for the Seebeck coefficient versus log͑t͒, since S ϳ ln͑p͒ through Eq. ͑2͒.…”
supporting
confidence: 87%
“…This is in contrast to the Ca 2+ ions for which a shift to more positive binding energies was observed. Furthermore, this was in contrast to the interactions in most complexes and reservoir compounds used in conjunction with iodine; no formation of tri-iodide or penta-iodide as reported in the literature for other iodine complexes has been found [19,20]. The lack of a detectable shift in the binding energy for iodine in the iodine-silicate composite sample could be attributed to the limited range of emitted photoelectron binding energies exhibited by this element in the presence of alkali metals [34].…”
Section: X-ray Photoelectron Spectroscopycontrasting
confidence: 64%
“…Reservoir materials are based on the tendency of iodine to form charge transfer complexes with various organic molecules, the best known of which are complexes with starch [19]. For most complexes the formation of tri-iodide, I À 3 , and penta-iodide, I À 5 , ions is a requirement [19,20]. During studies aimed at the development of paint formulations with disinfectant properties, it was noted that iodine is readily absorbed by and released from nano-structured calcium silicate hydrate (NCaSilH) [21].…”
Section: Introductionmentioning
confidence: 99%
“…During this long time the so-called intermediate regime of diffusion should be obtained. [8] We found that after iodine diffusion for 48 h, the pentacene structure was completely changed. We confirmed this by XRD measurements where the XRD peak corresponding to the thin-film phase ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…A further reduction of the iodine concentration leads to still better structural film properties: After decreasing the time of iodine diffusion to 10 min (sample A10) we obtained the socalled intermediate regime of diffusion [8] which is characterized by the presence of the thin-film phase and also its intercalate phase in the layer. Both the measured XRD peaks corresponding to these phases are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%